Bone-targeting AAV-mediated silencing of Schnurri-3 prevents bone loss in osteoporosis - Yeon-Suk Yang (Nature Portfolio, 2019)
The adaptor protein SHN3 suppresses new bone formation by controlling osteoblast activity. Here, the authors show that ablation of SHN3 function, either genetically or by delivering an artificial miRNA via AAV9, rescues bone loss in osteoporotic mice, and show that engineering of the AAV9 capsid improves targeting to bone